Synergy Between State Administrative Law And Criminal Law In Asn Discipline Enforcement: Sinergi Hukum Administrasi Negara Dan Hukum Pidana Dalam Penegakan Disiplin Asn - Maybellina Beatrix; Vrestissya Septiani Rahmadiana; Zahra Wati Qhoiri (Academia Open, 2026)
General Background: Discipline enforcement among State Civil Apparatus (ASN) constitutes a fundamental pillar of clean and accountable governance within a constitutional state framework. Specific Background: In practice, disciplinary violations by ASN frequently intersect with criminal law, particularly in cases involving abuse of authority, corruption, and misconduct that threaten public trust, creating risks of overlapping authority and sanctions. Knowledge Gap: Existing discussions often address administrative and criminal mechanisms separately, leaving uncertainty regarding their coordinated application in ASN discipline enforcement. Aims: This study examines the relationship between State Administrative Law and Criminal Law in enforcing ASN discipline through a normative juridical approach based on administrative governance regulations and Government Regulation Number 94 of 2021. Results: The findings demonstrate that the two legal regimes operate in a complementary manner, with administrative law functioning as a supervisory and corrective framework, while criminal law is applied when violations exceed administrative boundaries and cause public harm. Novelty: This research emphasizes the principle of ultimum remedium as the primary normative basis for determining sanction priority, positioning criminal sanctions as a last legal measure. Implications: The study provides structured guidance for civil service development authorities and law enforcement institutions to ensure proportional, coordinated, and legally certain handling of ASN disciplinary violations within an integrated governance system. Highlights • Administrative sanctions operate as the primary supervisory mechanism in ASN discipline handling• Criminal proceedings are reserved for violations exceeding administrative responsibility and public interest thresholds• The ultimum remedium principle structures sanction prioritization within a layered accountability system Keywords ASN Discipline; State Administrative Law; Criminal Law; Ultimum Remedium; Public Governance